Pembinaan Atlet Federasi Triathlon Indonesia Jawa Tengah Dalam Menghadapi Pekan Olahraga Nasional XXI Aceh Sumut Tahun 2024 - iik suryati; Ripto Susilo (JURNAL TRANSMA, 2025)
This study aims to identify the organizational conditions, coaching, human resource management, training programs, and facilities for the Central Java Triathlon Federation in preparing for the 21st National Sports Week in Aceh and North Sumatra in 2024. The research conducted is a quantitative descriptive study.The subjects in this study are 5 members of the Central Java Provincial KONI, 5 members of the Central Java FTI, 5 triathlon coaches from Central Java, and 5 triathlon athletes from Central Java. In the data collection technique, the researcher used a questionnaire given to the respondents. The data analysis techniques used include validity tests, reliability tests, and descriptive percentage analysis techniques. From the research conducted, it can be concluded that (1) the condition of the organization of the Central Java Provincial Board of the Indonesian Triathlon Federation is in very good condition with a percentage of 84%. (2) The condition of the triathlon athlete development in Central Java Province is in very good condition with a percentage of 85%. (3) The condition of human resource management of the Indonesian Triathlon Federation in Central Java is in good condition with a percentage of 76%. (4) The condition of the triathlon athlete training program in Central Java Province is in very good condition with a percentage of 85%. (5) Meanwhile, the condition of the facilities and infrastructure of the Indonesian Triathlon Federation in Central Java is in good condition with a percentage of 77%.